An Analysis of Regional Ozone Pollution Generation and Intercity Transport Characteristics in the Yangtze River Delta - Yu Cao; Jinghui Ma; Xiaoyi Wang; Juanjuan Bian (Atmosphere)
Understanding the relative contributions of regional transport and local generation, alongside the nonlinear relationships between ozone (O3) and its precursors, is essential for formulating effective O3 pollution control strategies. The Yangtze River Delta region experiences pronounced O3 pollution transmission between cities, with pollutants capable of spreading hundreds of kilometers downwind under varying wind, temperature, and humidity conditions. However, the distributional characteristics of regional O3 pollution transmission across different cities within this area remain unclear. This study applies the Texas Commission on Environmental Quality method to assess the spatial distribution of regional background and locally generated ozone concentrations, while using a composite analysis to examine the wind and temperature field characteristics during typical years of high ozone transport and local generation episodes. The results indicate that ozone concentrations across regions are strongly influenced by local wind anomalies, with elevated temperatures correlating with high O3 concentrations. Furthermore, an algorithm based on observed O3 concentrations and ground-level wind data was developed to quantify pollution transport rates more accurately, addressing uncertainties in pollutant transport dynamics due to variable wind fields and identifying “false” potential source areas. The findings reveal that intercity transport within the Yangtze River Delta contributes 45.2–65.1% to regional O3 levels, exceeding local generation in impact. Shanghai experiences the highest transmission influence (over 50%), while Zhejiang Province shows a dominant local generation influence (below 20%). In Anhui Province, O3 concentrations are notably high, with significant internal transport and substantial transmission to Jiangsu Province. This study offers valuable insights into the pathways, traceability, and three-dimensional wind field characteristics of O3 pollution across cities in the Yangtze River Delta, elucidating the dynamic mechanisms necessary for mitigating O3 pollution transmission in diverse urban settings.